The Sun and the Troposphere Control the Earth’s Temperature - Lightfoot, H. Douglas; Ratzer, Gerald (Journal of Basic & Applied Sciences, 2023)
The basis for this study is the flow of energy from the Troposphere to space and the role that water vapor and carbon dioxide (CO2) play in affecting the flow. Then, it analyzes the radiation profiles and compares them to the ratio of water molecules to CO2 molecules. Examining the radiation profiles of water vapor and CO2 showed the overlap made it virtually impossible to separate the warming effects. Calculating the ratio of water vapor molecules to CO2 molecules by proven physics and chemistry is accurate for separating the individual warming effects. The results of a quantitative examination show water vapor has 1,000 to 7,000 times more impact on the Earth’s temperature than CO2. The warming effect of CO2 versus concentration is linear. In contrast, the warming effect of water vapor versus concentration is curved. The lowest level of the atmosphere, the Troposphere, has most of the air mass and water vapor and exercises control over the Earth’s temperature. Energy leaving the Troposphere flows virtually unhindered to space. The Sun is Earth’s primary energy source, and its natural variations control its temperature.